No need for labels: the autofluorescence of Leishmania Tarentolae mitochondria and the necessity of negative controls - Eckers, Elisabeth; Deponte, Marcel (PLOS ONE, 2012)
Background Fluorescence microscopy is a powerful tool to study the morphology and function of subcellular compartments or to determine the localization of proteins. The method is also regularly used for the analysis of parasitic protists including kinetoplastida. Results Here, we report a significant autofluorescence of Leishmania tarentolae mitochondria. The autofluorescence, presumably caused by flavoproteins, was detectable using a variety of cell fixation protocols and had a maximum emission at approximately 538 nm. Stable signals were obtained with xenon lamps as a light source and filter sets that are commonly used for the detection of green fluorescent protein. Conclusions On the one hand, we present a methodological approach to examine mitochondrial morphology or to study the colocalization of mitochondrial proteins without additional staining or labeling procedures. On the other hand, under certain experimental conditions, mitochondrial autofluorescence can result in false positive signals, demonstrating the necessity to analyze unlabeled cells as negative controls.
Gesehen am 16.04.2019